Exploring the role of macrophages in the progression from atypical hyperplasia to endometrial carcinoma through single-cell transcriptomics and bulk transcriptomics analysis - Song, Xiaolei; Na, Re; Peng, Nianghai; Cao, Wenming; Ke, Yan (Frontiers in Endocrinology, 2023)
Introduction In this study, we aimed to identify key genes in endometrial cancer by conducting single-cell analysis of macrophages. Methods We sourced clinical data from the TCGA database as well as supplementary datasets GSE201926 and GSE173682. Using bulk-seq data of atypical endometrial hyperplasia and endometrial cancer, we pinpointed key differentially expressed genes. Single-cell RNA sequencing was utilized for further gene expression analysis. Cluster analysis was conducted on TCGA tumor data, identifying two distinct subtypes. Statistical methods employed included LASSO regression for diagnostic modeling and various clustering algorithms for subtype identification. Results We found that subtype B was closely related to cellular metabolism. A diagnostic model was established using LASSO regression and was based on the genes CDH18, H19, PAGE2B, PXDN, and THRB. This model effectively differentiated the prognosis of cervical cancer. We also constructed a prognosis model and a column chart based on these key genes. Discussion Through CIBERSORT analysis, CDH18 and PAGE2B were found to be strongly associated with macrophage M0. We propose that these genes influence the transformation from atypical endometrial hyperplasia to endometrial cancer by affecting macrophage M0. In conclusion, these key genes may serve as therapeutic targets for endometrial cancer. A new endometrial cancer risk prognosis model and column chart have been constructed based on these genes, offering a reliable direction for future cervical cancer treatment.